Transparency of Business and the Achievement of Sustainable Development Goals in Ukraine - Inna Berzhanir; Anatolii Berzhanir; Liubov Shachkovska; Bondaruk Ihor; Osadchuk Nataliia (Communications of International Proceedings, 2021)
The development of a modern market economy involves the introduction of business transparency. Of particular importance is the problem of business transparency in terms of conducting socially responsible business, which can be implemented only in case of economic decision-making transparency, taking into account the social and environmental consequences for entrepreneurs and society. Business itself is interested in ensuring openness, as its information transparency significantly affects the formation of its reputation in the market. The most detailed, accessible and objective information about the company's activities, in particular, the effectiveness of its financial indices, is one of the important criteria for attracting investment. Ensuring sustainable development is forcing more and more companies to implement appropriate tools in their corporate governance systems, which include the creation of public corporate reporting. In modern conditions, sustainable development and corporate social responsibility are necessary components of economic activity and strategic development of companies. Principles of sustainable development should be laid down in the strategy of business structures. To ensure the openness and transparency of their activities, they must adhere to the principles of transparency – they have introduced regular information to stakeholders and reporting on the effectiveness of corporate social responsibility. Submission of reports on sustainable development to stakeholders provides transparency, provides an opportunity to assess the effectiveness of the company's business processes.
Keywords: Transparency of Business; Stakeholders; Sustainable Development; Companies.